A Comparison between Respiratory Factors in Patients with Vocal Nodule and Normal Controls - E Abbassi; S Jalai; P Meraji (Vesnu Publications, 2008)
• Background:Speech is the most important communication tool and is the smooth product of four systems: respiratory, phonatory, resonatory, and articulatory. Currently, a variety of voice disorder occurred because of life style and environmental pollutants. Vocal nodule is one of the most prevalent disorders in this category. Considering the point that the air required for vocal cords vibration is supplied by respiratory system and we repeatedly confront with inappropriate respiratory factors in patients with vocal nodules, this study was carried out to compare respiratory factors in patients with vocal nodule and normal controls. • Materials and Methods:In this study, 14 patients with vocal nodule and 7 healthy subjects referred from a medical specialist were examined. Vital capacity, vital volume and tidal volume of patients and controls were measured by PCLX, LX-strobe and ST 1 dysphonia while making voice with high, normal and low frequencies. The data were analyzed using Fisher and Mann-Withny tests. • Results:The results showed that there was significant difference between patients with vocal nodule and healthy controls on all measured factors. However, there was no relationship between family background and vocal nodule. • Conclusion:Patients with vocal nodule do not seem to have problem with the volume of their lungs. Probably high tension in their respiratory muscles during speaking causes them not to be able to use the full capacity of their lungs and this creates a short of tidal volume and as a result, a problem in their phonatory system, i.e., vocal nodule. Because of small sample size, we need to be cautious in generalizing the results. • Key words: Vocal nodule, respiratory factors, phonatory system